2011
DOI: 10.1098/rsta.2010.0339
|View full text |Cite
|
Sign up to set email alerts
|

The Anthropocene: a new epoch of geological time?

Abstract: Anthropogenic changes to the Earth’s climate, land, oceans and biosphere are now so great and so rapid that the concept of a new geological epoch defined by the action of humans, the Anthropocene, is widely and seriously debated. Questions of the scale, magnitude and significance of this environmental change, particularly in the context of the Earth’s geological history, provide the basis for this Theme Issue. The Anthropocene, on current evidence, seems to show global change consistent with the suggestion tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
223
0
26

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(250 citation statements)
references
References 23 publications
1
223
0
26
Order By: Relevance
“…R. Soc. B 282: 20142990 with the Industrial Revolution [43][44][45]. However, other authors suggested that anthropogenic changes may have begun in the Early Holocene [46] or even the latest Pleistocene [47], and a compelling case has been made for the pre-industrial roots of anthropogenic alterations in the global marine ecosystem [7].…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 282: 20142990 with the Industrial Revolution [43][44][45]. However, other authors suggested that anthropogenic changes may have begun in the Early Holocene [46] or even the latest Pleistocene [47], and a compelling case has been made for the pre-industrial roots of anthropogenic alterations in the global marine ecosystem [7].…”
Section: Discussionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (Parry et al, 2007) stated bluntly: "The resilience of many ecosystems is likely to be exceeded this century by an unprecedented combination of climate change, associated disturbances (e.g., flooding, drought, wildfire, insects, ocean acidification), and other global change drivers (e.g., land use change, pollution, overexploitation of resources)". The human species has become so dominant that some argue we have entered a new geological age dominated not by the chemical and physical workings of the earth as they exist under their own motion from time to time but by us humans and they propose we call this new period the Anthropocene (Zalasiewicz et al, 2011). This is not new.…”
Section: Introductionmentioning
confidence: 99%
“…This increasing global footprint of human activities on the biosphere has led some to use the term 'the Anthropocene' , to denote the present period of anthropogenically induced global environmental change 3 . The ongoing oceanic absorption of atmospheric CO 2 has helped to restrict present global warming by reducing the total amount of manmade CO 2 in the atmosphere.…”
mentioning
confidence: 99%